Permittivity properties of nickel zinc ferrite-oil palm empty fruit bunch-polycaprolactone composite - Ahmad, Ahmad Fahad; Abbas, Zulkifly; Obaiys, Suzan J.; Ibrahim, Nor Azowa; Zainuddin, Mohamad Faiz; Salem, Aeshah (Elsevier, 2016)
The dielectric properties of composites based on nickel-zinc-ferrite (NZF) filler can be improved by the addition of various types of materials. Amongst others, ferrite–polymer composites have been subjected to wide range of research, due to their extensive applications: electromagnetic interference shielding, microwave absorption, electrodes and sensors. In this study, Ni0.5Zn0.5Fe2O4 (NZF) was prepared via conventional solid-state method. While NZF–OPEFB-PCL composite has been prepared via the mechanical milling mode and then characterized by X-ray powder diffraction. Dielectric properties of the composite, such as dielectric constant, loss factor and loss tangent were measured at different filler percentage over a wide range of frequency (0.20MHz-20 GHz). An open ended coaxial probe connected to a vector network analyzer (VNA) was utilized for the evaluation of dielectric properties for materials and composites under test at the room temperature. Both dielectric constant and loss factor values increased due to the filler increment in the polymer matrix, where the composition of 15% NZF gives the extreme permittivity value at the used microwave frequency. Furthermore, the obtained results confirmed that dielectric properties of the composite can be controlled by the proper loading and the wise filler choosing. The adjusted properties support the purpose of polymer composite materials for microwave and communicational applications.